LEGAL PROTECTION OF OWNERSHIP OF FLATS UNITS AGAINST FOREIGN NATIONALS IN INDONESIA - Putu Kharisa Pramudya; I Made Pria Dharsana (NOTARIIL Jurnal Kenotariatan, 2023)
This paper analyzes the legal protection of ownership of apartment units against foreign nationals in Indonesia. The focus of the study in this paper is the ambiguity of protection and legal certainty in the provisions of Article 144 of the Copyright Law jo. Article 71 paragraph (1) PP No. 18 of 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration, which regulates the granting of Ownership Rights to Flat Units to foreigners over HGB and use rights if land rights are not extended. The method used is a normative legal research approach, namely a statutory approach and a conceptual approach. As an analytical tool for the legal issues studied, the author uses the theory of legal certainty, the theory of legal protection and the theory of justice. The legal materials used are primary legal materials in the form of legislation, which are complemented by secondary legal materials in the form of reputable journals and the latest literature. The results that can be concluded in this study are the Job Creation Act and PP No. 18 of 2021 does not stipulate if the rights to the land that are the basis of the apartment are not extended or renewed, so that it does not reflect the existence of legal certainty over the ownership of flats by foreigners. This also has implications for the legal protection that will be obtained by foreigners, so that foreigners may lose money when buying flats in Indonesia, because their bargaining position is weaker in Indonesian land law. The purpose of this analysis is to provide certainty and legal protection of ownership of flats for foreign nationals in Indonesia.